Geoquímica y tectónica de la secuencia terrígena mesozoica de la región de Tlalpujahua, Michoacán - Lerma Rodríguez, Omar (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The Tlalpujahua Region (TR) is located NE of Michoacan state and NW of Mexico state. In the TR outcrops the Zihuatanejo subterrane that is part of the Guerrero Terrane, which represents one of the largest tectonostratigraphic terrane of Mexico. Within the stratigraphic successions of the TR have been reported different sandstone sequences that represent an opportunity to determine the relationships of provenance and tectonic correlation of the TR. A sedimentary provenance study of the Psammites-Turbidites (Arkoses) San Pedro Sequence (TJ-PTASP) was performed, where this unit would represent the oldest sedimentary sequence and therefore represents the relative basement of the Cretaceous volcanic sedimentary sequence of the TR. For this study detailed geological sections of the locations reported for the Psammites-Turbidites (Arkoses) San Pedro Sequence (TJ-PTASP) were performed, as well as two more locations in San Lorenzo and Santa María Stream. The TJ-PTASP sequence is made up of a series of intercalations of fine to medium-grained siliciclastic sandstones, presenting variations in their primary structures, such as turbidity, of load, which reveal a deep basin deposit environment. Based on the petrographic analysis is observed a predominant abundance of quartz-feldspar and the important presence of metamorphic and granitic type lithic fragments. In conjunction with geochemical analysis, they have been classified as arkoses and quartz litharenites. Also, that the TJ-PTASP sequence comes from a passive continental margin and its composition is in contrast with the Coloradillas sandstones, which are greywackes and litharenites with volcanic influence. Based on the analysis of U-Pb in zircon concentrates, it was obtained that the ages of these detrital minerals correspond to the Precambrian, Paleozoic and Triassic, the last being the maximum sedimentation ages.

La Región de Tlalpujahua (RT) se localiza al NE del estado Michoacán y al NW del estado de México. En la RT aflora el subterreno Zihuatanejo que es parte del Terreno Guerrero, el cual representa uno de los terrenos tectonoestratigráficos más grandes de México. Dentro de las sucesiones estratigráficas de la RT se han reportado diferentes secuencias de areniscas que representan una oportunidad para determinar las relaciones de procedencia y correlación tectónica de la RT. Se realizó un estudio de procedencia sedimentaria de la Secuencia Psammitas-Turbiditas (Arcosas) San Pedro (TJ-PTASP), donde esta unidad representaría a la secuencia sedimentaria más antigua y por lo tanto representa al basamento relativo de la secuencia volcánica-sedimentaria Cretácica de la RT. Para este estudio se realizaron secciones geológicas a detalle de las localidades reportadas para la Secuencia Psammitas-Turbiditas (Arcosas) San Pedro (TJ-PTASP), así como dos localidades más en el Arroyo San Lorenzo y Santa María. La secuencia TJ-PTASP está constituida por una serie de intercalaciones de areniscas siliciclásticas de grano fino a medio, presentando variaciones en sus estructuras primarias, como turbididez, de carga, que nos revelan un ambiente de depósito de cuenca profunda. Con base en los análisis petrográficos se observa una predominante abundancia de cuarzo-feldespato y la presencia importante de fragmentos líticos de tipo metamórfico y granítico. En conjunto con los análisis geoquímicos, se han clasificado como arcosas y litoarenitas cuarzosas. También, que la secuencia TJ-PTASP proviene de un margen continental pasivo y su composición es contrastante con las areniscas Coloradillas, las cuales son grauvacas y litarenitas con influencia volcánica. Con base en análisis de U-Pb en concentrados de zircones, se obtuvo que las edades de estos minerales detríticos corresponden al Precámbrico, Paleozoico y Triásico, siendo estas últimas las edades máximas de sedimentación.
Instituto de Investigaciones en Ciencias de la Tierra. Maestría en Geociencias y Planificación del Territorio
Keywords: info:eu-repo/classification/cti/1; INICIT-M-2020-0666; Terreno Guerrero; Procedencia sedimentaria; Estructuras de turbidez; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4441